Protein O-GlcNAcylation in multiple immune cells and its therapeutic potential - Cai, Huanhuan; Xiong, Wei; Zhu, Haoyan; Wang, Qiongxin; Liu, Shi; Lu, Zhibing (Frontiers in Immunology, 2023)
O-GlcNAcylation is a post-translational modification of proteins that involves the addition of O-GlcNAc to serine or threonine residues of nuclear or cytoplasmic proteins, catalyzed by O-GlcNAc transferase (OGT). This modification is highly dynamic and can be reversed by O-GlcNAcase (OGA). O-GlcNAcylation is widespread in the immune system, which engages in multiple physiologic and pathophysiologic processes. There is substantial evidence indicating that both the hexosamine biosynthesis pathway (HBP) and O-GlcNAcylation are critically involved in regulating immune cell function. However, the precise role of O-GlcNAcylation in the immune system needs to be adequately elucidated. This review offers a thorough synopsis of the present research on protein O-GlcNAcylation, accentuating the molecular mechanisms that control immune cells' growth, maturation, and performance via this PTM.